Английский язык для студентов Института Электронного обучения учебное пособие - Богоряд Н. В. Наталия Владимировна; Демидова О. М. Ольга Михайловна; Дьяченко Ю. В. Юлия Васильевна; Лысунец Т. Б. Татьяна Борисовна; Чайка Ю. А. Юлия Александровна; Шатохина А. О. Анастасия Олеговна (Томск, 2016)
Заглавие с титульного экрана